1985
DOI: 10.3168/jds.s0022-0302(85)81243-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Natural Intramammary Corynebacterium bovis Infection on Milk Yield and Composition

Abstract: The objective was to assess effect of Corynebacterium bovis infection of the bovine mammary gland on milk yield and composition. Yield and composition of milk from 53 Corynebacterium bovis-infected quarters of 44 cows at four consecutive milkings were compared with those of the contralateral uninfected quarters. Differences between infected and uninfected quarters in milk, fat, and protein yield and in fat and protein content were small and statistically nonsignificant. Numbers of somatic cells were moderately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
2
8

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 9 publications
0
8
2
8
Order By: Relevance
“…In this study, Corynebacterium bovis was not accompanied by any degradation of milk production or composition, consistently with Le Van et al's study on natural infections [17]. In contrast, the lack of influence of Corynebacterium bovis on somatic cell count is not in accordance with the results from other studies involving natural infections [10,17,24], which revealed a slight increase in cell count in the presence of Corynebacterium bovis. But in these studies, the presence of clinical signs of mastitis was not taken into consideration although it could have explained the increase in somatic cell count.…”
Section: Discussioncontrasting
confidence: 37%
“…In this study, Corynebacterium bovis was not accompanied by any degradation of milk production or composition, consistently with Le Van et al's study on natural infections [17]. In contrast, the lack of influence of Corynebacterium bovis on somatic cell count is not in accordance with the results from other studies involving natural infections [10,17,24], which revealed a slight increase in cell count in the presence of Corynebacterium bovis. But in these studies, the presence of clinical signs of mastitis was not taken into consideration although it could have explained the increase in somatic cell count.…”
Section: Discussioncontrasting
confidence: 37%
“…Por outro lado, estes micro-organismos apresentam impacto limitado na produção e qualidade do leite (LEVAN; BERHART;ESLER, 1985;SCHUKKEN et al, 2009).…”
Section: Lista De Ilustraçõesunclassified
“…Quando não há necessidade de identificação do agente causador, a detecção de alteração na concentração dos componentes do leite também pode ser utilizada como forma de diagnóstico indireto à mastite (KITCHEN, 1981 (BRAMLEY, 1975;BROOKS;BARNUN, 1984;LEVAN;BERHART;ESLER, 1985;SORDILLO et al, 1989;POCIECHA, 1989;2005 Corynebacterium spp. já foi isolado em casos de mastite clínica e como responsável por alterações significativas em nível celular (COSTA et al 1985;SCHUKKEN et al 1989b;BOYER, 1998;HOGEVEEN, 1998).…”
Section: A Detecção Da Mastite Por Meio Dos Componentes Do Leiteunclassified
See 1 more Smart Citation
“…Esta espécie bacteriana é um dos mais importantes agentes etiológicos da mastite de vacas, cabras e ovelhas (MARK et al, 2005). Além disso, Staphylococcus aureus é conhecida por causar infecções de longa duração com tendência a se tornarem crônicas e com alta resistência aos antimicrobianos (MILES et al, 1992 (LEVAN et al,1985;POCIECHA, 1989), contrariamente, outros autores afirmam sua elevada prevalência em infecções intramamárias, sugerindo que talvez seja mais apropriado não considerá-lo um patógeno secundário (BUENO et al, 2003;PITKALA et al, 2004;MARTINS et al, 2010 Leveduras e fungos constituem a flora normal de solos e podem ser encontrados em uma ampla variedade de substratos, tais como plantas e água. A maioria destes microrganismos são oportunistas e as fontes de infecção também incluem a pele do úbere, a secreção de glândulas mamárias, mãos dos ordenhadores, utensílios e equipamentos de ordenha (RICHARD et al, 1980).…”
Section: Contagem Celular Somáticaunclassified